2022
DOI: 10.1093/mnras/stac1145
|View full text |Cite
|
Sign up to set email alerts
|

The chemo-dynamical groups of Galactic globular clusters

Abstract: We introduce a multi-component chemo-dynamical method for splitting the Galactic population of Globular Clusters (GCs) into three distinct constituents: bulge, disc, and stellar halo. The latter is further decomposed into the individual large accretion events that built up the Galactic stellar halo: the Gaia-Enceladus-Sausage, Kraken and Sequoia structures, and the Sagittarius and Helmi streams. Our modelling is extensively tested using mock GC samples constructed from the auriga suite of hydrodynamical simula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 117 publications
4
28
1
Order By: Relevance
“…11 The mass of this GC translates into M å host galaxy ≈ 1.3 × 10 9 M e for its former host galaxy. Such M å value is well within the literature range for GSE (see Figure 6) and is more than 10 times larger than the expected value for Sequoia of ∼5-8 × 10 7 M e (Myeong et al 2019;Forbes 2020;Kruijssen et al 2020;Callingham et al 2022). Following this line of thought, it would be natural to imagine GSE as a stronger candidate as the host of such a robust NSC.…”
Section: The Case Of ωCen and Ngc 1851supporting
confidence: 82%
See 2 more Smart Citations
“…11 The mass of this GC translates into M å host galaxy ≈ 1.3 × 10 9 M e for its former host galaxy. Such M å value is well within the literature range for GSE (see Figure 6) and is more than 10 times larger than the expected value for Sequoia of ∼5-8 × 10 7 M e (Myeong et al 2019;Forbes 2020;Kruijssen et al 2020;Callingham et al 2022). Following this line of thought, it would be natural to imagine GSE as a stronger candidate as the host of such a robust NSC.…”
Section: The Case Of ωCen and Ngc 1851supporting
confidence: 82%
“…These authors demonstrated that GCs of GSE, selected from dynamics alone, follow a track in AMR clearly separated from their in situ counterparts, being more metal-poor within the same age interval (data from Forbes & Bridges 2010). These results were confirmed and expanded with new DRs from Gaia by many subsequent studies (Massari et al 2019;Forbes 2020;Horta et al 2020;Kruijssen et al 2020;Callingham et al 2022).…”
Section: Candidates In the Literaturesupporting
confidence: 61%
See 1 more Smart Citation
“…Using established mass-metallicity relations (see Kirby et al 2013), the total stellar mass of the progenitor dwarf before disruption can be gleaned from the typical metallicity of its stellar population (Belokurov et al 2018;Feuillet et al 2019;Naidu et al 2021). An independent mass constraint can be obtained by scaling up the total number of GCs associated with the merger (Myeong et al 2018c(Myeong et al , 2019Massari et al 2019;Forbes 2020;Callingham et al 2022). A third method of constraining the total stellar mass is via the analysis of the GS/E chemical pattern (e.g., Fernández-Alvar et al 2018;Helmi et al 2018;Mackereth et al 2019;Vincenzo et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They did, however, identify three massive satellite progenitors for the ex-situ globular cluster population. This includes a galaxy dubbed "Kraken", to which they attribute 40% of ex-situ globular clusters (Kruijssen et al 2020;Callingham et al 2022). Other techniques based on Machine Learning algorithms, such as boosted decision trees have been utilized on the scale of individual stars by Veljanoski et al (2018) to identify MW halo stars.…”
Section: Introductionmentioning
confidence: 99%